When 'substandard' is the standard, who decides what is appropriate? Exploring healthcare provision in Cambodia. Issue 4 (8th August 2019) - Gryseels, Charlotte; Kuijpers, Laura Maria Francisca; Jacobs, Jan; Peeters Grietens, Koen
ABSTRACT: Cambodia has experienced an impressive economic growth in the last two decades that has not been matched by equal investments in public health care. In combination with other historical and sociocultural factors, this has led to a set of private and public health care practices that divert from standards of clinical good practice. Based on qualitative data collected in malaria and (para)typhoid fever projects, we will describe falsified laboratory test results, dubious diagnostic practices of both unlicensed and licensed doctors, the sales of substandard preparations and combinations of medicines, and even surgeries for commercial interest instead of patient well-being. Patients navigate this complex medical landscape by circumventing costly clinical care – by self-diagnosing and self-medicating, using medicines bought from drug sellers – and by actively seeking out clinical interventions when the required financial investment is perceived to match the illness severity. We will explore what practices constitute healthcare in urban and rural Cambodian settings; what differentiates these practices from clinical 'good practice' guidelines in conventional medicine; and which mechanisms patients, drug sellers and medical doctors have developed to navigate a health care system that at the same time enables, encourages, and sanctions such unregulated practices.